Computational Work with Very Large Text Collections - John Unsworth (Journal of the Text Encoding Initiative)
This essay will address the challenges and possibilities presented to the Text Encoding Initiative, particularly in the area of interoperability, by the very large text collections (on the order of millions of volumes) being made available for computational work in environments where the texts can be reprocessed into new representations, in order to be manipulated with analytical tools. It will also consider TEI’s potential role in the design of these environments, these representations, and these tools. The argument of the piece is that interoperability is a process as well as a state, that it requires mechanisms that would sustain it, and that TEI is one of those mechanisms.